2016
DOI: 10.1128/aem.02063-16
|View full text |Cite|
|
Sign up to set email alerts
|

Intracellular pH Response to Weak Acid Stress in Individual Vegetative Bacillus subtilis Cells

Abstract: Intracellular pH (pH i ) critically affects bacterial cell physiology. Hence, a variety of food preservation strategies are aimed at perturbing pH i homeostasis. Unfortunately, accurate pH i quantification with existing methods is suboptimal, since measurements are averages across populations of cells, not taking into account interindividual heterogeneity. Yet, physiological heterogeneity in isogenic populations is well known to be responsible for differences in growth and division kinetics of cells in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In previous studies, pHluorin was used to investigate membrane homoeostasis of Escherichia coli and Bacillus subtilis following acid stress (Martinez et al, 2012), proton leakage through the MotA/B proton channel of the flagellar apparatus of Salmonella enterica (Morimoto et al, 2010), or the effect of potassium uptake on metabolism of Staphylococcus aureus (Gries et al, 2016). Moreover, pHluorin has been successfully used in B. subtilis both on population and single cell level to study antibacterial effects of weak organic acids to assess their potential as food preservation strategies (Ter Beek et al, 2015; Pandey et al, 2016). In the present study, we investigated the potential of pHluorin to assess membrane-damaging activity of bacteriocins in L. monocytogenes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, pHluorin was used to investigate membrane homoeostasis of Escherichia coli and Bacillus subtilis following acid stress (Martinez et al, 2012), proton leakage through the MotA/B proton channel of the flagellar apparatus of Salmonella enterica (Morimoto et al, 2010), or the effect of potassium uptake on metabolism of Staphylococcus aureus (Gries et al, 2016). Moreover, pHluorin has been successfully used in B. subtilis both on population and single cell level to study antibacterial effects of weak organic acids to assess their potential as food preservation strategies (Ter Beek et al, 2015; Pandey et al, 2016). In the present study, we investigated the potential of pHluorin to assess membrane-damaging activity of bacteriocins in L. monocytogenes .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, expression of pHluorin is a convenient approach to identify and test novel antimicrobial compounds active against L. monocytogenes and other (human) pathogens. Additionally, L. monocytogenes EGD-e/pNZ-P help -pHluorin and derivatives in combination with fluorescence ratio imaging microscopy (Martinez et al, 2012; Pandey et al, 2016) can be exploited for infection research to study the mechanisms of pH-homeostasis of L. monocytogenes e.g., in highly acidic phagosomes/phagolysosomes macrophages and other host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such flexibility occurs in B. cereus spores ( Van Melis et al, 2014 ). It would be interesting and important to find out whether culture heterogeneity also plays a role in the responses of B. cereus toward acid stress and low oxygen tension ( Pandey et al, 2016 ). Overall, it is expected that investigations of the stress physiology of B. cereus will continue to be central to understanding its behavior in challenging environments.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we found that the residual pyruvate acidified the extracellular pH (pH ex ) and intracellular pH (pH in ), with the lowest pH ex and pH in being 5.7 and 6.0 for BSGN12 during fermentation. The pH in critically affects bacterial cell physiology, such as protein synthesis and enzyme activity [710]. The activity of Ce GNA1 is pH-dependent with an optimum pH of 8.2, which is similar to other GNA1 homologues that generally function in alkaline conditions (pH 7.4–9.7), thus it is crucial to maintain intracellular pH homeostasis for the enhanced activity of Ce GNA1 and improved production of GlcNAc [4].…”
Section: Introductionmentioning
confidence: 99%